Effects of varying water consumption on spinach (Spinacia oleracea L.) sustainable cultivation / Nur Atiqah Husaifuna … [et al.] - Husaifuna, Nur Atiqah; Wan Ahmed, Wan Natasya; Hani, Nurul Wahida; Othman, Hamizah (Universiti Teknologi MARA, Sabah, 2024)
Water is a raw material used in various biochemical processes inside plants, making it a crucial element for plant development and growth. Understanding the appropriate amount of water consumption is vital to prevent plants from experiencing abiotic stress such as waterlogging and water stress. Leafy vegetables, such as spinach (Spinacia oleracea), require more water than other vegetables. Therefore, this study aimed to determine the optimal amount of water necessary for sustainable spinach cultivation and to assess the effects of different irrigation regimes on spinach growth and yield. Four different irrigation treatments with four replications were applied: T0 (600 ml), T1 (700 ml), T2 (800 ml), and T3 (900 ml). Significant differences (p-value < 0.05) were observed for plant height, number of leaves, root length, soil oxygen levels, and the fresh and dry weight of spinach when irrigated with 700 ml of water (T1). The highest spinach yield (fresh weight = 9.64 g) was achieved with adequate water supply (T1), while the yield (fresh weight = 0.78 g) was lower at a higher water consumption level (T3). This suggests sustainable cultivation of spinach due to the optimal yield obtained with lower water consumption.